Informing the research agenda for optimizing audit and feedback interventions: results of a prioritization exercise - Colquhoun, Heather L.; Carroll, Kelly; Eva, Kevin W.; Grimshaw, Jeremy M.; Ivers, Noah; Michie, Susan; Brehaut, Jamie C. (BMC medical research methodology, 2021)
Background Audit and feedback (A&F) interventions are one of the most common approaches for implementing evidence-based practices. A key barrier to more effective A&F interventions is the lack of a theory-guided approach to the accumulation of evidence. Recent interviews with theory experts identified 313 theory-informed hypotheses, spread across 30 themes, about how to create more effective A&F interventions. In the current survey, we sought to elicit from stakeholders which hypotheses were most likely to advance the field if studied further. Methods From the list of 313, three members of the research team identified 216 that were clear and distinguishable enough for prioritization. A web-based survey was then sent to 211 A&F intervention stakeholders asking them to choose up to 50 ‘priority’ hypotheses following the header “ A&F interventions will be more effective if…” . Analyses included frequencies of endorsement of the individual hypotheses and themes into which they were grouped. Results 68 of the 211 invited participants responded to the survey. Seven hypotheses were chosen by > 50% of respondents, including A&F interventions will be more effective… “ if feedback is provided by a trusted source” ; “ if recipients are involved in the design/development of the feedback intervention” ; “ if recommendations related to the feedback are based on good quality evidence” ; “ if the behaviour is under the control of the recipient” ; “ if it addresses barriers and facilitators (drivers) to behaviour change” ; “ if it suggests clear action plans” ; and “ if target/goal/optimal rates are clear and explicit” . The most endorsed theme was Recipient Priorities (four hypotheses were chosen 92 times as a ‘priority’ hypotheses). Conclusions This work determined a set of hypotheses thought by respondents to be to be most likely to advance the field through future A&F intervention research. This work can inform a coordinated research agenda that may more efficiently lead to more effective A&F interventions.